Access to care of frail community-dwelling older adults in Belgium: a qualitative study. (2019) - Fret, Bram; De Donder, Liesbeth; Lambotte, Deborah; Dury, Sarah; Van der Elst, Michaël; De Witte, Nico; Switsers, Lise; Hoens, Sylvia; Van Regenmortel, Sofie; Verté, Dominique
Abstract: Aim: This paper aims to identify barriers that frail community-dwelling older adults experience regarding access to formal care and support services. Background: Universal access to healthcare has been set by the World Health Organisation (WHO) as a main goal for the post-2015 development agenda. Nevertheless, regarding access to care, particular attention has to be paid to the so-called vulnerable groups, such as (frail) older adults. Methods: Both inductive and deductive content analyses were performed on 22 individual interviews with frail, community-dwelling older adults who indicated they lacked care and support. The coding scheme was generated from the conceptual framework '6A's of access to care and support' (referring to work of Penchansky and Thomas, 1981; Wyszewianski, 2002; Saurman, 2016) and applied on the transcripts. Findings: Results indicate that (despite all policy measures) access to a broad spectrum of care and support services remains a challenge for older people in Belgium. The respondents' barriers concern: 'affordability' referring to a lot of Belgian older adults having limited pensions, 'accessibility' going beyond geographical accessibility but also concerning waiting lists, 'availability' referring to the lack of having someone around, 'adequacy' addressing the insufficiency of motivated staff, the absence of trust in care providers influencing 'acceptability', and 'awareness' referring to limited health literacy. The discussion develops the argument that in order to make care and support more accessible for people in order to be able to age in place, governments should take measures to overcome these access limitations (eg, by automatic entitlements) and should take into account a broad description of access. Also, a seventh barrier (a seventh A) within the results, namely 'ageism', was discovered.